Manajemen Pembiayaan Pendidikan di SD Plus Al Hikmah Kab. Kediri - Lia Roikhanatus Sa’adah; M. Hanif Satria Budi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Can’t be denied that implementation of a learning program’s in the school institution about problem of financing or funding is an important thing. Because funding have an effect to the smoothness and achievement of a programs. The processing of implementation learning in a school institution will work effectively if if supported by good financing. But not only that, an existing financial management must be good and clear so that the funds can be used to the maximum. Beside that, supervision of financial management needs to be done to minimize errors that may occur. The aims of this research is to find out about management of financing in the Al Hikmah Emelentary School especially about source of funds and financial accountability. The methode used in this research is Research, documenter and interview with the people who involved. From the result of data, an overviews about management financing system. Management of financing in the Al Hikmah elementary school Kediri is professional and effective. About the funding needed for the school activity is sufficient. Beside that, all about funding that received by elementary school of Al Hikmah and financial accountability is always reported to the people or institution that involved. And also all the funding can be used for the needs of school activities.